Crimigração : a relação entre política migratória e política criminal no Brasil - Moraes, Ana Luisa Zago de (2015)
The Brazilian migration policy initially was related to colonization, and migrants were considered useful for the population and agricultural work. The objective of criminal policy was to control the slaves and their descendants, criminalizing their way of life, fights and sports, like “capoeira”, and using the deportation against them. In the First Republic, immigration started to be related with anarchism. In this context, the immigration policy started to be directed to restriction of entrance, and the deportation became an administrative measure destinated to the political enemies of the republic. During the Vargas Era, the repression of “foreigners” has increased: no more nominated “migrants”, as in the times of colonization. It had already started the appreciation of the national worker and the prohibition of entry of undesirable, which led to persecution of communists, anarchists and prostitutes. During the civil military dictatorship, the doctrine of national security was consolidated and adapted to migration policy, in a "safe migration" policy. In this period, criminal law was not destinated to the repression of immigrants, but criminal policy has adopted postulates of national security to combat enemies, and the war on drugs and against the international drug smugglers. Based on this, we investigate the crimmigration since the last democratic transition and constitutional promotion of human rights. For these objectives, we consider migrants as fundamental rights holders, but also victims of transnational vulnerabilities and control and criminalization by the states. Added to this, we reflect about transitional justice for a democratic immigration policy, guided in human rights and non-criminalization.